Morphometric and meristic analyses of Randall’s threadfin bream Nemipterus randalli Russell, 1986 along the Indian coast - Srihari, Murugesan; Pradhan, Suraj Kumar; Pavan-Kumar, Annam; Bhushan, Shashi; Nayak, Binaya Bushan; Sreekanth, G. B.; Abidi, Zeba Jaffer (Indian Journal of Fisheries, 2020)
Nemipterus randalli Russell, 1986 is one of the commercially important demersal fish in Indian waters. The present study was designed to understand the morphometric and meristic variations between the stocks of N. randalli along the Indian coast. A total of 450 samples were collected from 5 maritime states during September 2018 to November 2018. A total of 19 morphometric and 9 meristic traits were extracted and subjected to statistical analyses. Factor analysis showed that morphometric characteristics like eye diameter, head length, pre-pectoral length, post-orbital length, anal fin length and caudal peduncle depth were significant in separating the stocks. Discriminant function analysis showed a high re-classification success rate of 80.43%. Kruskal-Wallis test of meristic traits revealed lack of difference between the stocks. Results indicated the presence of different phenotypic stocks along the Indian coast and therefore the need for separate management strategies for sustaining the catch of N. randalli in the future.Keywords: Demersal fish, Factor analysis, Management, Phenotypic plasticity, Stock